KEPRIBADIAN TOKOH UTAMA NOVEL 9 SUMMERS 10 AUTUMNS KARYA IWAN SETYAWAN - Hajar Arohmah; Nugraheni Eko Wardani; Edy Suryanto (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
The research aims to describe (1) structure of novel 9 Summers 10 Autumns by Iwan Setyawan; (2) characteristic of main character personality on novel 9 Summers 10 Autumns by Iwan Setyawan; (3) the value of character education on novel 9 Summers 10 Autumns by Iwan Setyawan; and (4) the relevance of novel 9 Summers 10 Autumns by Iwan Setyawan as literature learning materials in SMA. This research is a qualitative studying using descriptive qualitative and document analysis. The data sources are document and informant. The technique sampling of this research using purposive sampling. Data validity test uses irangulation theory. Data analysis text use interactive method. The result shows (1) structure of novel 9 Summers 10 Autumns by Iwan Setyawan have a correlation; (2) Iwan as main character fill of mature personality criterias by Gordon Allport; (3) novel 9 Summers 10 Autumns have fiveteen types representation the value of character education; and (4) novel 9 Summers 10 Autumns fill criteria as a good literature learnings material.